Pengaturan Tanggungjawab Puskesmas Sikumana dalam Pengelolaan Limbah Medis di Tinjau dari Peraturan Menteri Kesehatan Nomor 18 Tahun 2020 tentang Pengelolaan Limbah Medis - Kesya Alfa Rambu Hana Tonga; Yohanes G. Tuba Helan; Rafael Rape Tupen (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to analyze the regulation of the responsibility of Sikumana Health Center in managing medical waste in review of the Minister of Health Regulation Number 18 of 2020 concerning Medical Waste Management. The research method used in this research is empirical juridical research, namely research based on applicable laws and regulations and data obtained in the field. The results of the study provide information that the Regulation of the Minister of Health. Number 18 of 2020 regulates medical waste management which includes reduction, sorting, storage, transportation, utilization, processing, and supervision, comparison of the responsibilities of Sikumana Health Center with Permenkes No. 18 of 2020 can be seen that, Sikumana Health Center has carried out some of its responsibilities in medical waste management in accordance with Permenkes No. 18 of 2020. However, there are still some shortcomings in terms of storage, utilization, and processing of medical waste. Sikumana Health Center has carried out the reduction and sorting of medical waste in temporary shelters (TPS) properly, the storage of medical waste in TPS has not met the standards, such as the absence of room separation and the absence of complete personal protective equipment (PPE) in terms of transporting medical waste from TPS to the medical waste processing site (TPPLM) is carried out by a third party who has an official permit in terms of supervision of medical waste management at Sikumana Health Center is carried out by the Kupang City Health Office periodically this is a factor that is the most frequent obstacle in medical waste management.